Preparation of Organo-Vermiculite by Modification with Hexadecyltrimethylammonium Bromide Under Microwave Irradiation - Cai, Yan-Hua (Asian Journal of Chemistry, 2011)
Organo-vermiculite (OVMT) was prepared by modification reaction of vermiculite (VMT) with hexadecyltrimethylammonium bromide (CTAB) under microwave irradiation. The structure and properties of organo-vermiculite were investigated by X-ray diffraction (XRD), fourier infrared spectroscopy (FT-IR), thermal gravimetric analysis (TGA) and scanning electron microscopy (SEM). The XRD and FT-IR results indicated that CTAB successfully interacted with the vermiculite layer by the microwave irradiation. Scanning electron microscopy showed that the order structure of the vermiculite layer has been destroyed due to intercalation of the CTAB. Simultaneously, the investigation also showed that this intercalation reaction method using microwave irradiation was feasible and has some particular advantages such as simple manipulation, shorter reaction time, etc., finally, the intercalation mechanism under microwave irradiation was discussed.